Digitalizing the Planning of our Grids. Talk - Schlüter, Alexander

Kulturelles Trauma und polyphones Gedächtnis. Zur Thematisierung des Genozids an den Armenien bei Elif Safak und Dogan Akhanli - Schulte Eickholt, Swen (Totenklage und Gedächtnis des Schreckens. Türken und Armenier 1915)
Aufbauend auf der Theorie von Jeffrey C. Alexander entwickelt der Artikel einen Begriff des kulturellen Traumas als irreparable Störung des kulturellen Deutungsgewebes eines Kollektivs. Am Beispiel der Romane "Der Bastard von Istanbul" (Safak) und "Die Richter des Jüngsten Gerichts" (Akhanli) werden Formen literarischen Gedächtnisses - im Sinne eines polyphonen Gedächtnisses - als Arbeiten am kulturellen Trauma thematisiert.
Keywords: kulturelles Trauma; Elif Shafak; Armenier; Aghet; Kulturelles Gedächtnis

The conductor density of local function fields with abelian Galois group - Klüners, Jürgen; Müller, Raphael (Journal of Number Theory)
We give an exact formula for the number of G-extensions of local function fields Fq((t)) for finite abelian groups G up to a conductor bound. As an application we give a lower bound for the corresponding counting problem by discriminant.
Keywords: Algebra and Number Theory

The conductor density of local function fields with abelian Galois group - Müller, Raphael; Klüners, Jürgen (Journal of Number Theory)

Reparaturbetrieb, Inklusion und Fachkräftesicherung – Transformation der Benachteiligtenförderung in Deutschland - Lippegaus, Petra; Heisler, Dietmar (Retrospektiven, Perspektiven & Synergien einer Historischen Berufsbildungs- & Wissenschaftsforschung)

Inklusion – Herausforderung für die Jugendberufshilfe - Lippegaus, Petra (In: Evangelische Jugendhilfe (EJ) Heft 2/2020)

Die Krisen und die Benachteiligtenförderung – ein Blick zurück nach vorn - Lippegaus, Petra (in: dreizehn. Zeitschrift für Jugendsozialarbeit)

Geschlecht als pädagogische Herausforderung?! Eine diskursanalytische Studie über den wissenschaftlichen Diskus zu der Frage der Bedeutung von Geschlecht für das Lehren und Lernen in der Schule - Daniel-Söltenfuß, Desiree

Lernen auf Distanz – Einblicke in den familialen Alltag des Homeschoolings und Formen der Bewältigung - Gerhardts, L.; Kamin, A.M.; Meister, Dorothee M.; Richter, L.; Teichert, Jeannine (Medienimpulse)

Entwicklung von Selbstlern- und Medienkompetenz im Homeschooling – Chancen und konzeptionelle Anforderungen - Gerhardts, L.; Kamin, A.M.; Meister, Dorothee M.; Richter, L.; Teichert, Jeannine (PraxisForschungLehrer*innenBildung)

Ich habe auch Facebook-Freunde“ – Erinnerungspraktiken in vergangenen Freundschaften - Teichert, Jeannine (merzWissenschaft)

VI Elia - Bergmann, Claudia Dorit (Gottesdienste mit Kindern 2021)

Bienen und Honig im Alten Testament. - Bergmann, Claudia Dorit (Deutsches Bienenjournal)

Essen für Heute und Morgen: Die Kommende Welt in frühjüdischen Texten - Bergmann, Claudia Dorit (Geist und Leben)

Inter-surface maps via constant-curvature metrics - Schmidt, Patrick; Campen, Marcel; Born, Janis; Kobbelt, Leif (ACM Transactions on Graphics)
We propose a novel approach to represent maps between two discrete surfaces of the same genus and to minimize intrinsic mapping distortion. Our maps are well-defined at every surface point and are guaranteed to be continuous bijections (surface homeomorphisms). As a key feature of our approach, only the images of vertices need to be represented explicitly, since the images of all other points (on edges or in faces) are properly defined implicitly. This definition is via unique geodesics in metrics of constant Gaussian curvature. Our method is built upon the fact that such metrics exist on surfaces of arbitrary topology, without the need for any cuts or cones (as asserted by the uniformization theorem). Depending on the surfaces' genus, these metrics exhibit one of the three classical geometries: Euclidean, spherical or hyperbolic. Our formulation handles constructions in all three geometries in a unified way. In addition, by considering not only the vertex images but also the discrete metric as degrees of freedom, our formulation enables us to simultaneously optimize the images of these vertices and images of all other points.

Bézier guarding - Mandad, Manish; Campen, Marcel (ACM Transactions on Graphics)
We present a mesh generation algorithm for the curvilinear triangulation of planar domains with piecewise polynomial boundary. The resulting mesh consists of regular, injective higher-order triangular elements and precisely conforms with the domain's curved boundary. No smoothness requirements are imposed on the boundary. Prescribed piecewise polynomial curves in the interior, like material interfaces or feature curves, can be taken into account for precise interpolation by the resulting mesh's edges as well. In its core, the algorithm is based on a novel explicit construction of guaranteed injective Bézier triangles with certain edge curves and edge parametrizations prescribed. Due to the use of only rational arithmetic, the algorithm can optionally be performed using exact number types in practice, so as to provide robustness guarantees.

Combinatorial Construction of Seamless Parameter Domains - Zhou, Jiaran; Tu, Changhe; Zorin, Denis; Campen, Marcel (Computer Graphics Forum)
Abstract The problem of seamless parametrization of surfaces is of interest in the context of structured quadrilateral mesh generation and spline‐based surface approximation. It has been tackled by a variety of approaches, commonly relying on continuous numerical optimization to ultimately obtain suitable parameter domains. We present a general combinatorial seamless parameter domain construction, free from the potential numerical issues inherent to continuous optimization techniques in practice. The domains are constructed as abstract polygonal complexes which can be embedded in a discrete planar grid space, as unions of unit squares. We ensure that the domain structure matches any prescribed parametrization singularities (cones) and satisfies seamlessness conditions. Surfaces of arbitrary genus are supported. Once a domain suitable for a given surface is constructed, a seamless and locally injective parametrization over this domain can be obtained using existing planar disk mapping techniques, making recourse to Tutte's classical embedding theorem.

Efficient piecewise higher-order parametrization of discrete surfaces with local and global injectivity - Mandad, Manish; Campen, Marcel (Computer-Aided Design)

Intergenerationelle Beziehungen in der Familie - Buhl, Heike M.; Sommer, Sabrina (Psychotherapie im Alter)
Beziehungen zwischen Erwachsenen und ihren Eltern sind durch Interdependenzen und Dependenzen gekennzeichnet. Während das Zusammenleben von Familien mit Kindern im mittleren Erwachsenenalter dabei ganz überwiegend durch Interdependenz geprägt ist, nehmen im Alter Dependenzen durch gesundheitliche Beeinträchtigungen der Eltern zu. Mit Blick darauf werden im Artikel behaviorale, kognitive und emotionale Merkmale von Eltern-Kind-Beziehungen erläutert und theoretisch in zentrale Konzepte eingebettet. Das Verhalten ist durch Solidarität zwischen den Generationen, aber auch durch Aspekte des Einflusses innerhalb der Beziehung und aufeinander, gekennzeichnet. Um Familienkognitionen zu beschreiben, werden die verwandten Konzepte der Individuation und der filialen Reife herangezogen. Verhalten, wie auch Kognitionen, sind eng mit dem dritten Beziehungsmerkmal, der Affektivität verknüpft, das neben positiven auch negative Gefühle sowie Ambivalenzen umfasst.
Keywords: General Earth and Planetary Sciences; General Environmental Science

Psychologie als Unterrichtsfach: Konzeption des Curriculums an der Universität Paderborn - Buhl, Heike M.; Scharlau, Ingrid; Patrzek, Justine; Hiller, Sara; Klingsieck, Katrin B. (Psychologiedidaktik und Evaluation XIII)
Keywords: Unterrichtsfach Psychologie